1997
DOI: 10.1080/00926239708403932
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy and quality of life among sexually dysfunctional men and women

Abstract: This study evaluated the associations between intimacy, quality of life, and sexual dysfunction in men and women. Participants were 145 sexually functional (43 men, 102 women) adults drawn from the general population and 198 sexually dysfunctional (114 men, 84 women) adults who came to a university sexual behavior clinic. All respondents were currently involved in a heterosexual relationship. Respondents completed a series of questionnaires to evaluate the level of intimacy in their relationships, their qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 13 publications
8
90
0
2
Order By: Relevance
“…For example, it has been shown in previous studies that men with ED report deficits in several broader areas of their life, including their general emotional satisfaction, general happiness, productivity, intimacy and safety. 17,20 The psychological and QOL findings of the present study support the recent proposal by FuglMeyer et al 18 that presence of ED has its impact on men's QOL because of the creation of a sexual aspiration-achievement gap. According to FuglMeyer et al, 18 when sex is regarded as an important aspect of a man's life, but he is unable to fulfil his sexual goals (for example, through presence of ED), the gap between sexual aspirations and achievement widens, resulting in an overall decline in QOL.…”
Section: Discussionsupporting
confidence: 80%
“…For example, it has been shown in previous studies that men with ED report deficits in several broader areas of their life, including their general emotional satisfaction, general happiness, productivity, intimacy and safety. 17,20 The psychological and QOL findings of the present study support the recent proposal by FuglMeyer et al 18 that presence of ED has its impact on men's QOL because of the creation of a sexual aspiration-achievement gap. According to FuglMeyer et al, 18 when sex is regarded as an important aspect of a man's life, but he is unable to fulfil his sexual goals (for example, through presence of ED), the gap between sexual aspirations and achievement widens, resulting in an overall decline in QOL.…”
Section: Discussionsupporting
confidence: 80%
“…For some men, particularly older men, emotional connection was integral to their arousal. This finding is supported by other research which suggests that relationship factors may be equally important to men's sexual functioning (McCabe, 1997). In a study focusing on the relationship between sexual desire and relationship functioning among community couples, Brezsnyak and Whisman (2004) found that higher levels of marital satisfaction predicted higher levels of sexual desire for husbands as well as for wives.…”
Section: Introductionsupporting
confidence: 56%
“…There is strong theoretical support, and some empirical support, for the supposition that women's sexual arousal is closely linked to their satisfaction with their partner and their relationship (Basson, 2000;Byers, 2001; The Working Group for a New View of Sexual Women's Sexual Problems, 2001). McCabe (1997) evaluated the differences in levels of intimacy between sexually functional and dysfunctional males and females and found women experienced sexual dysfunction even if only a few intimacy-related domains were lacking. For men, most aspects of intimacy had to be impaired before dysfunction occurred.…”
Section: Discussionmentioning
confidence: 99%
“…4 This is despite the fact that PE causes similar issues as ED within a relationship, namely, reduced sexual satisfaction and intimacy, and increased interpersonal difficulties. [5][6][7][8] Levels of female sexual dysfunction (FSD) are also relatively high, with epidemiological data suggesting rates of 20-60%. 2,9-11 A recent review of prevalence studies investigating female sexual difficulty conducted by Hayes et al 12 observed that although variation exists, patterns of sexual dysfunction were consistent across studies.…”
Section: Introductionmentioning
confidence: 99%